Uniqueness theorems for L-functions in the extended Selberg class - Hao Wen-Jie; Chen Jun-Fan (Open Mathematics, 2018)
In this paper, we obtain uniqueness theorems of L-functions from the extended Selberg class, which generalize and complement some recent results due to Li, Wu-Hu, and Yuan-Li-Yi.